Specialize or diversify? And in what? Trade composition, quality of specialization and persistent growth - Giovanni Dosi; Federico Riccio; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This paper, using a long-term, product-level cross-country dataset, analyzes the trade-growth nexus by introducing two novel indicators able to capture demand and supply attributes of countries' quality of specialization. The Keynesian efficiency index measures demand attractiveness of the export baskets, estimating product-level demand elasticities and weighting them by diversification; the Schumpeterian efficiency index tracks the export basket' technological dynamism proxied by product-level patent intensities. These two dimensions of quality of specialization are effective in explaining the rate and volatility of growth and the duration of growth episodes, identified as periods longer than 8 years of 2% average growth and, even more, of exceptional growth episodes (Ï5%). Our results, robust to a wide range of control variables, suggest that specialization per sé is detrimental for growth resilience while countries with a diversified export structure, specialised either in demand-elastic and technological-dynamic productions are likely to experience longer growth episodes.
Keywords: F41; O11; O14; 330; Structural Change; International Trade; Growth Episodes